Queering Socialist Realism: Serhii Parajanov’s Early Ukrainian Films and his Transition to Poetic Cinema - Olga Briukhovetska (Наукові записки Наукма: Історія і теорія культури)
The article argues that Serhii Parajanov’s lesser-known early Ukrainian films, created within the constraints of socialist realism, subtly challenged Soviet normativity, including heteronormativity. These works are characterized as a “double failure” — both artistic and ideological — as they reveal the operations of Parajanov’s creative desires, foreshadowing the queer aesthetics that would later define his mature poetic cinema. Focusing on The Flower on the Stone (1962), Parajanov’s final film before his creative breakthrough, the article identifies two key disruptions of the heteronormative framework of socialist realism: gender fluidity and an inversion of the Soviet Bildungsroman. Through moments of disorientation and subversions of ideological clarity, the film exposes the artificiality of Soviet norms while suggesting alternative modes of being. Employing the concept of a sexual-aesthetic nexus, the article contends that Parajanov’s sexuality — criminalized and used as a pretext for his politically motivated persecution — should be understood as an integral yet distinct part of his creative desires.